STUDI IMPLEMENTASI MANAJEMEN RISIKO PADA PT ASURANSI MULTI ARTHA GUNA TBK PERIODE 2020-2024 - Indri Iswardhani (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
This study analyzes the implementation of risk management at PT Asuransi Multi Artha Guna Tbk for the 2020-2024 period using a qualitative descriptive approach with content analysis of annual and sustainability reports. The results show that the company has implemented risk management consistently and structurally through four main pillars. Risk identification is carried out participatively through a risk register with 9 risk categories according to POJK No.44/POJK.05/2020. Risk measurement includes sensitivity analysis of exchange rates, market prices of securities, credit quality, and IBNR. Risk monitoring is conducted in tiers through regular committee meetings and analysis of asset-liability maturity profiles, indicating a strong liquidity position. Insurance risk mitigation is executed through prudent underwriting policies and comprehensive reinsurance strategies through proportional and non-proportional programs. The company's soundness level is rated 2 (healthy) with RBC consistently above 120% and is able to manage limited litigation cases without material impact. The consistency of risk management implementation effectively maintains risk profile stability and supports sustainable business growth.